Legal Assistance as Workers Rights in the Banking Industry - I Made Arta Negara; Siti Hajati Hoesin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Law in Indonesia guarantees legal protection for workers. However, its existence does not necessarily mean that employment problems do not occur. So that the presence of Legal Aid is considered very important for a country with the principle of equality before the law. Therefore, there is a right that will be obtained by all levels of Indonesian society, namely equality before the law. This study aims to examine legal aid as a worker's right in the banking industry. This type of research is normative law research. Normative legal research is legal research conducted by examining library materials or secondary data and referring to legal concepts. The results of this study that the implementation of legal aid will be very helpful when workers in the banking industry are faced with legal cases or with a collection of state instruments that carry out judicial power and court proceedings. Every worker/labor has the right to get protection on to safety and health work; Moral and decency; and Treatment which in accordance with dignity and dignity man as well as values religion.